Dialektika Filsafat, Masyarakat, dan Kebudayaan: Tinjauan Konstruksi Nilai dan Implikasinya dalam Transformasi Pendidikan Modern: The Dialectic of Philosophy, Society, and Culture: A Review of Value Construction and Its Implications for the Transformation of Modern Education - Asthadi Mahendra Bhandesa; I Putu Gede Sutrisna; I Gusti Agung Tresna Wicaksana; Ni Luh Putu Kartiningsih (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2026)
This article examines the dialectical relationship between philosophy, society, and culture in the context of modern educational transformation in Indonesia. This study is motivated by the emergence of a cultural identity crisis stemming from globalization and digitalization, which have influenced the younger generation's value orientations. This research aims to analyze the relationships among philosophy as a foundation of values, society as a space for social practice, and culture as a collective manifestation, with implications for the contemporary education system. The study uses a qualitative approach, employing a systematic literature review of scientific articles from Google Scholar, Scopus, and ERIC databases over the past 10 years. The analysis is carried out in stages: identification, selection, theme categorization, and conceptual synthesis of relevant literature. The results of the study indicate that education detached from society's philosophical and cultural roots tends to lose social relevance and fails to shape students' character as a whole. The dialectic among philosophy, society, and culture provides an important foundation for culture-based education responsive to global challenges. The implications of this research emphasize the importance of strengthening a curriculum grounded in local wisdom, implementing culturally responsive teaching, and transforming teachers' roles as mediators of values and agents of social change. This article concludes that the dialectical relationship between philosophy, society, and culture plays a fundamental role in shaping a relevant, humanistic, and sustainable education system. Education rooted in philosophical values ??and local cultural wisdom can strengthen students' identity, character, and adaptive abilities amidst the challenges of globalization and digitalization.